THE MARITIME SECURITY COOPERATION SOMALIA-CHINA IN COMBATING PIRACY IN SOMALIA’S WATERS (2008-2024) - Lubis, Lia Aulia; Sembiring, Afri Emilia Br; Perwita, Anak Agung Banyu (Jurnal Pertahanan dan Bela Negara, 2025)
This research examines the relationship between Somalia’s maritime security cooperation with China in combating piracy in Somali waters, particularly the Gulf of Aden and the Indian Ocean, from 2008 to 2024. The main objective of this research is to analyze the impact of bilateral cooperation between the two countries on reducing the threat of piracy, maritime security capabilities, and the broader implications for national and regional stability in Somalia. Using a qualitative case study methodology with secondary data obtained from official government documents, United Nations reports, international organization reports, scientific publications, and credible national media. Data analysis was conducted through content analysis of the development of China’s naval strategy, the impact of piracy on socio-economics, and the role of multilateral cooperation within the framework of international relations and maritime security theory. The research findings indicate that the People’s Liberation Army Navy (PLAN) has evolved from a mission focused on protection to participating in joint patrols and multilateral exercises, which significantly reduced piracy between 2009 and 2018. This cooperation will impact the improvement of Somalia’s maritime security capabilities and post-conflict economic recovery, and help stabilize the regional area. This aligns with China’s strategic goals mentioned in the Belt and Road Initiative (BRI). The piracy rate in Somalia from 2019 to 2023 was relatively low due to the implementation of continuous naval patrols, increased coast guard capacity, and the integration of maritime cooperation for broader economic recovery under the Belt and Road Initiative framework. However, in 2024, piracy rates resurfaced, indicating the need for sustained cooperation, adaptive strategies, and the integration of military diplomacy into Somalia’s foreign policy.